2010
DOI: 10.1007/s00467-010-1513-2
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity C-reactive protein and mean platelet volume in paediatric hypertension

Abstract: The purpose of the study was to investigate serum uric acid (SUA), high-sensitivity C-reactive protein (hs-CRP) and mean platelet volume (MPV) in pre-hypertensive (PH) and hypertensive (HT) children and adolescents. The study group consisted of 80 patients aged 10-19 years subdivided into PH and HT groups according to mean daytime or night-time systolic or diastolic blood pressure (BP) levels (> 90th percentile, but < 95th percentile and > or = 95th percentile, respectively). The control group (C) contained 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…In pediatric subjects with prehypertension and hypertension, Wasilewska et al demonstrated a strong positive correlation between MPV and UA. Using linear regression analysis, they showed that an increase of 1 mg/dL in UA levels was associated with an average increase of 0.27 fL in MPV [23]. In patients with nonalcoholic fatty liver disease, Shin et al also reported a positive correlation between MPV and UA [24].…”
Section: Discussionmentioning
confidence: 93%
“…In pediatric subjects with prehypertension and hypertension, Wasilewska et al demonstrated a strong positive correlation between MPV and UA. Using linear regression analysis, they showed that an increase of 1 mg/dL in UA levels was associated with an average increase of 0.27 fL in MPV [23]. In patients with nonalcoholic fatty liver disease, Shin et al also reported a positive correlation between MPV and UA [24].…”
Section: Discussionmentioning
confidence: 93%
“…Another interesting finding was the negative correlation between MPV and plasma lipid levels, which is considered a major cardiovascular risk factor. Although several studies have previously shown the association between MPV and hypertension, 14,15,21,22 its relationship in subjects without hypertension is unknown. The latest studies have shown that prehypertension causes platelet activation, as demonstrated by increased MPV.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, recent studies have showed that platelet depletion resulted in a significant inhibition of allergen-induced airway hyperresponsiveness, and it was found to be more effective in suppressing airway remodeling processes than the administration of a glucocorticosteroid [47]. Previous studies showed that there were no changes in MPV levels and no negative associations between MPV and CRP in asthmatic children [21], but a genome-wide association study revealed that there are different mechanisms in childhood asthma and adult asthma [48,49,50,51]. Further investigations on the role of activated platelets in asthma may be beneficial in the search for therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%